(untitled) (Journal of Ideas in Health, 2023)
Background: Variants of SARS-CoV-2 have been detected along with the worldwide COVID-19 transmission. Insufficient data exists regarding SARS-CoV-2 variants in Iraq, particularly concerning travelers at Iraqi border crossings. This study aimed to screen SARS-CoV-2 variants among individuals entering Iraq from Turkey through the Ibrahim Khalil international border checkpoint. Methods: A total of 116 (52 females, 64 males) COVID-19-positive cases from June 6, 2021, to July 30, 2021, were randomly selected from the Ibrahim Al-Khalil border crossing point between Turkey and Iraq. The patients were Iraqis tested positive for COVID-19 through nasopharyngeal and oropharyngeal swab collections. The confirmation of SARS-CoV-2 cases involved RNA extraction and real-time reverse transcription polymerase chain reaction (RT-PCR), following the World Health Organization guidelines. All samples were subjected to variant detection using the reverse transcription RT-PCR method. The RNA was extracted using a Zybio nucleic acid extraction kit and the RT-PCR was conducted using SARS-CoV-2 S-gene mutation detection RT-PCR kit. Results: In the 116 patients, we detected variants B.1.1.7, B.1.617.1.2, B.1.617.1.3, and Omicron sub-lineages (B.1.1.529, BA.1) at frequency rates of 13, 16, 45, and 36 cases, respectively. The highest prevalence rate was the delta variant among the tested subjects (38.8%) followed by the Omicron sub-lineages (B.1.1.529, BA.1) at 31%. Conclusion: This finding, which is the first of its kind at the northern Iraqi border checkpoint, suggests that these two variants could be a source of COVID-19 circulating in the Duhok province in Iraq. Additional studies are warranted across the country’s border entry points.